IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 19 TAHUN 2016 MENGENAI RENCANA KEBUTUHAN BARANG MILIK DAERAH (RKBMD) PADA SEKRETARIAT DAERAH PROVINSI RIAU TAHUN 2023 - Putri, T. Rika Fahira; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The implementation of the Minister of Home Affairs Regulation Number 19 of 2016 concerning the regional government asset needs plan at the Riau Provincial Secretariat has been carried out, but obstacles were encountered during the preparation process. This was due to several factors affecting its implementation, hindering the procurement and maintenance of regional assets. This disruption impacted the performance of Secretariat employees, as these assets are crucial for their work. This research aims to describe the implementation and the factors influencing the implementation of the Minister of Home Affairs Regulation Number 19 of 2016 concerning the regional government asset needs plan at the Riau Provincial Secretariat. This study employed a qualitative method with a descriptive research design to provide a detailed account of the research object and analyze the observed phenomena through interviews, observations, and document review. Primary and secondary data were collected from informants and documents. Data collection techniques included interviews, observations, and documentation. Data analysis involved data reduction, data display, and verification (conclusion drawing). Several obstacles were identified in the preparation process of the regional government asset needs plan, including the failure to analyze the sudden damage of new assets, unexpected revisions from bureaus within the Secretariat, sudden and urgent requests from superiors without prior analysis, and the time-consuming process of obtaining data from the Planning Division and the Technical Activity Implementing Officer. This research concludes that the implementation of the Minister of Home Affairs Regulation Number 19 of 2016 concerning the Regional Government Asset Needs Plan at the Riau Provincial Secretariat in 2023 was successfully implemented, and solutions for the identified influencing factors have been found. Keywords: Implementation; Regional Government Asset Needs Plan (RKBMD); Regional Secretariat; and Home Affairs Ministerial Regulation